The pass-through of exchange rate changes to import prices - Uwe Ketelsen; Mika Kortelainen (Bank of Finland, 1996)
In this paper, we analyze the empirical relevance of exchange rate pass-through for Finland, Sweden and Denmark during the period 1980-1994.Further, we attemp to determine if there has been a structural change in the pass-through relationship in 1990s.We find that about half the changes in exchange rates and world prices are passed through to import prices within one year, and three-quarters of such changes are passed through to import prices in two years.Moreover, there are no major differences among countries.Parameter constancy tests indicate the possibility of a structural change where the pass-through has slowed in recent years.Possible explanations of this are that the exchange rate regime has changed and competition has increased.
URN:NBN:fi:bof-20140807520
Keywords: 330; exchange rate pass-through; import prices; structural change